A policy brief on improving the lifestyle of women with polycystic ovary syndrome - Mouloud Aghajani Delavar; Sedighe Esmaeilzadeh; zeinab farhadi; Parvaneh Mirabi (Babol University of Medical Sciences, 2024)
Polycystic ovary syndrome (PCOS) in women is a significant public health issue. We searched the relevant databases using the sensitive keywords to receive the available evidence for successful lifestyle interventions among PCOS women. The systematic reviews related to PCOS were evaluated for an effective lifestyle intervention that was identified. The lifestyle interventions include three components: weight management, physical exercise, and behavioral coaching or combined interventions for developing exercise and modifying diet. Evidence shows that the impact of starting lifestyle intervention as the first-line management to improve obstetric and reproductive outcomes is high. There is evidence that proves health coaching can improve health behaviors and lifestyle. Thus, it is recommended to improve the lifestyle of women with PCOS.